srinvas

posted by .

solve ;2 xsquare y-3 xsquare+4 y=2010

  • srinvas -

    2x^2y - 3x^2 + 4y = 2010
    y(2x^2+4) = 2010 + 3x^2
    y = (2010+3x^2)/(2x^2+4)
    = 3/2 + 1002/(x^2+2)

    now what?

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Maths

    Write the following expression into its simplest form?
  2. math

    solve the following system of equations algebraically or graphically for x and y: y=xsquare-6x+6 y-x=-4 For an algebraicc solution, show your work here. y=x^2-6x+6 y-x= -4 Let's substitute x-4 for y in the first equation. x-4 = x^2-6x+6 …
  3. math

    2xsquare -8x -42 over 6xsquare divided by xsquare -9 over xsquare -3x in simplist form
  4. 9th grade

    whats the answer for xsquare+12x+20=0
  5. CALCULUS

    Y=(XSQUARE + 1 OVER XSQUARE - 1) CLOSE PARENTHESIS TO THE 3 POWER...
  6. pure maths

    Factorize Xsquare-6x-3
  7. ssc maths

    2 xsquare y -3 xsquare+ 4 y=2010
  8. math

    3-xsquare<=g(x)<=3secx for all x find lim xtends to0g(x)
  9. math

    TRY THIS EXPONENTIAL EQUATION 4(2^Xsquare)=8^X
  10. math

    Please help me now. SOLVE THE EXPONENTIAL EQUATION BELOW. 4(2^Xsquare)=8^X

More Similar Questions